RhizoPot platform: A high-throughput in situ root phenotyping platform with integrated hardware and software - Zhao, Hongjuan; Wang, Nan; Sun, Hongchun; Zhu, Lingxiao; Zhang, Ke; Zhang, Yongjiang; Zhu, Jijie; Li, Anchang; Bai, Zhiying; Liu, Xiaoqing; Dong, Hezhong; Liu, Liantao; et al. (Frontiers in Plant Science, 2022)
Quantitative analysis of root development is becoming a preferred option in assessing the function of hidden underground roots, especially in studying resistance to abiotic stresses. It can be enhanced by acquiring non-destructive phenotypic information on roots, such as rhizotrons. However, it is challenging to develop high-throughput phenotyping equipment for acquiring and analyzing in situ root images of root development. In this study, RhizoPot platform, a high-throughput in situ root phenotyping platform integrating plant culture, automatic in situ root image acquisition, and image segmentation, is proposed for quantitative analysis of root development. About one to five plants (maximum plant height; 1.0 meters) can simultaneously grow in each RhizoPot, and the longest growth period depends on the type of plant and environmental conditions. The imaging control software (RhizoAuto) can automatically and non-destructively image the roots of RhizoPot-cultured plants based on the set time and resolution (50-4800 dpi) and obtain high-resolution (>1200 dpi) images in batches. The improved DeepLabv3+ tool was used for batch processing of root images. The roots were automatically segmented and extracted from the background for analysis of information on radical features using conventional root software (WinRhizo and RhizoVision Explorer). Root morphology, root growth rate, and lifespan analysis were conducted using in situ root images and segmented images. The platform illustrates the dynamic response characteristics of root phenotypes in cotton. In conclusion, the RhizoPot platform has the characteristics of low cost, high efficiency, and high throughput. Therefore, it can effectively monitor the development of plant roots and realize the quantitative analysis of root phenotypes in situ.